Performance evaluation of high-performance self-compacting concrete with waste glass aggregate and metakaolin. (15th May 2023) - Meraz, Md Montaseer; Mim, Nusrat Jahan; Mehedi, Md Tanjid; Noroozinejad Farsangi, Ehsan; Shrestha, Rajesh Kumar; Kader Arafin, Sk Abdul; Bibi, Tayyaba; Hussain, Md Shakhaoat; Billah, Md Mustakim; Bhattacharya, Badhon; Aftab, Md Reduan; Paul, Sujon Kumar; et al.
Abstract: High-Performance Self-Compacting Concrete (HPSCC) has attracted much attention in recent decades due to its remarkable ability to fill formworks with densely packed reinforcing bars while requiring minimal or no external compaction. Because of the negative environmental impacts of cement and natural aggregates in concrete production, a much more sustainable alternative to manufacturing HPSCC is required. Recycled glass waste is one of the most attractive waste materials that can be used to create sustainable concrete compounds, which is currently a major area of study among researchers. This study aims to develop information not only about the fresh, mechanical, and durability characteristics of HPSCC, evaluate the environmental impact and correlate the crushing strength using a non-destructive approach by utilizing waste glass aggregates at replacement percentages of 0%, 10%, 20%, 30%, and 40%. To improve the performance of the produced HPSCC, Metakaolin was also added. The results of the fresh concrete tests revealed that the substitution of an optimal level of waste glass with Metakaolin provides adequate implementation in flowability, passing ability, and viscosity behaviors. Even though there is a reduction in the mechanical performance with glass aggregates, Metakaolin significantly improved strength and ductility by up to 16.12% and 15.91%, respectively. Furthermore, in most cases, the use of glass aggregates with Metakaolin significantly alters the durability properties of concrete while minimizing the environmental impact as well as the overall project cost. Finally, the NDT assessment demonstrates that the analytical equation can efficiently predict the compressive strength and promising to use for field application. Highlights: Waste glass aggregates were used for the production of HPSCC. Assessment of HPSCC by DT and NDT was correlated. It is recommended to use metakaolin with increasing percentages of crushed glass aggregates to enhance performance. In-situ strength of HPSCC was estimated using the Schmidt rebound hammer. The environmental impacts of HPSCCs were investigated.